Quando nem a palavra é de prata, nem o silêncio é de ouro. Análise de conflitos sobre mineração em Portugal - Matos, Ana Raquel; Fernandes, Lúcia (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2019)
This paper analyzes eight cases of mining conflicts in Portugal, focusing on the protest actions triggered, as well as the impacts they have produced. Methodologically, documentary analysis was undertaken. The results revealed collective action as the available resource for the affected populations to communicate their perceptions and arguments about the problems felt and to make their lived situations visible. Protest actions registered were able to produce legislative changes, even concerning specific situations, and gave visibility to the particularities of each case.